Signaling Pathways Implicated in Carbon Nanotube-Induced Lung Inflammation - Dong, Jie (Frontiers in Immunology, 2020)
Inflammation is a tissue response to a variety of harmful stimuli, such as pathogens, irritants, and injuries, and can eliminate insults and limit tissue damage. However, dysregulated inflammation is recognized as a cause of many human diseases, exemplified by organ fibrosis and cancer. In this regard, inflammation-promoted fibrosis is commonly observed in human lung diseases, such as idiopathic pulmonary fibrosis and pneumoconiosis. Carbon nanotubes (CNTs) are a type of nanomaterials with unique properties and various industrial and commercial applications. On the other hand, certain forms of CNTs are potent inducers of inflammation and fibrosis in animal lungs. Notably, acute inflammation is a remarkable phenotype elicited by CNTs in the lung during the early acute phase post-exposure; whereas a type 2 immune response is evidently activated and dominates during the late acute and chronic phases, leading to type 2 inflammation and lung fibrosis. Numerous studies demonstrate that these immune responses involve distinct immune cells, various pathologic factors, and specific functions and play crucial roles in the initiation and progression of inflammation and fibrosis in the lung exposed to CNTs. Thus, the mechanistic understanding of the immune responses activated by CNTs has drawn great attention in recent years. This article reviews the major findings on the cell signaling pathways that are activated in immune cells and exert functions in promoting immune responses in CNT-exposed lungs, which would provide new insights into the understanding of CNT-induced lung inflammation and inflammation-driven fibrosis, the application of CNT-induced lung inflammation and fibrosis as a new disease model, and the potential of targeting immune cells as a therapeutic strategy for relevant human lung diseases.